محددات التشغيل في الجزائر : أثر المتغيرات المؤسساتية و الاقتصادية الكلية - مصباحي إحسان; بوريش لحسن (جامعة الوادي University Of Eloued, 2024)
This study aims to highlight the most important intitutional and macroeconomic variables affecting the employment rate in Algeria during the period (1991-2021) using the vector autoregressive model (VAR). The study also presented the most important causes of unemployment, furthermore the most prominent efforts made by the state in order to confronting the imbalance in the labor market and finding solutions to this crisis. The results of this study showed that oil prices have a significant impact on raising employment rate in Algeria compared to the impact of expenditure on education and wages.
Determinants of employment in Algeria : Impact of institutional and macroeconomic variables
Keywords: التشغيل; البطالة; المتغيرات المؤسساتية; أسعار البترول; كتلة الأجور; employment; Institutional variables; Oil prices; Expenditure on education; Wages